The existing characteristics, transport patterns, and significance of nanoparticulate pollutants in groundwater surrounding an industrial park - Guai Hu; Zeyu Wang; Yixiang Xie; ZiXia Lin (PLoS ONE, 2025)
Nanoparticles, increasingly recognized by regulators and the public, have become potential pollutants in various media, including water. Water security, a pressing global issue, is exacerbated by industrialization, with industrial wastewater being a significant contributor to water pollution. This study collected nanoparticles from groundwater samples in residential areas surrounding the Mingzhu Industrial Park in Guangdong Province, China. To understand their characteristics as potential pollutants in wastewater and the information they provide, field emission transmission electron microscopy (TEM) was used to analyze the composition, elemental content, morphology, and crystal structure of the nanoparticles. The nanoparticles originated from three sources: factories, water pipes, and the natural environment. They aggregate and oxidize during transport, ensuring their stability in water. This study elucidates the characteristics and transport patterns of particulate pollutants in groundwater near industrial parks, a prerequisite for assessing the hazards of nano-pollutants in natural environments. Additionally, it provides valuable insights for future discussions on their ecological impacts and advancements in water detection and treatment technologies.